COMPREHENSIVE APPROACH TO IMPROVING AUTOIMMUNE THROMBOCYTOPENIC PURPURA TREATMENT RESULTS - Gaybulla I. Mustafakulov; Farhod D. Ortiqboyev (Central Asian Journal of Medicine, 2023)
This article presents the experience of leading 224 patients with autoimmune thrombocytopenic purpura (ATP). Comparative data of results of inhalation and traditional methods of treatment with glucocorticoid hormones and operative method of treatment - splenectomy (SE) are given. It has been established that the use of glucorticosteroids (GCS) Cold metered inhalation hormones proved to be most effective in 87.2% of patients (compared to the conventional treatment method - 75.7%) and accelerated remission by 6.3 days. EC implemented by the in the early postoperative period was more effective in 96.9% of cases.